التشبه بالجنس الآخر في ثقافة الشعوب (Journal of the College of Basic Education, 2022)
Hardly a society is devoid of manifestations of imitating the opposite sex with the disparity between societies in quantity and quality, as imitating the opposite sex is an old phenomenon, and whoever follows what the old researchers wrote on this subject, finds various sayings, some of which lack evidence, being a kind of guesswork, A generalization that is not based on what is evidenced by it, and others consider resemblance to a behavior in which an animal resembles a human being. I will highlight in this research the resemblance to the opposite sex in the cultures of peoples, making the study into three sections. The manifestations of resembling men and women spread in Greek society greatly, and then the second study was devoted to the study of imitating the opposite sex in eastern civilization, Despite the few texts contained in the eastern sources, they are sufficient to demonstrate the prevalence of imitating the opposite sex. As for the third topic, it reviewed imitating the opposite sex in the Arab and Islamic countries, resulting from the expansion of Islamic conquests, and the entry of peoples into Islam of various nationalities, as well as the The large number of prisoners and slaves who were brought to Arab and Islamic countries helped spread the phenomenon of hermaphroditism and masculinization, as ignorance did not know it, nor did the first century AH, but luxury and a new civilization brought it.